The impact of pre‐eclampsia definitions on the identification of adverse outcome risk in hypertensive pregnancy – analyses from the CHIPS trial (Control of Hypertension in Pregnancy Study). (25th February 2021) - Magee, LA; Singer, J; Lee, T; Rey, E; Asztalos, E; Hutton, E; Helewa, M; Logan, AG; Ganzevoort, W; Welch, R; Thornton, JG; Woo Kinshella, ML; et al.
Abstract : Objective: To examine the association between pre‐eclampsia definition and pregnancy outcome. Design: Secondary analysis of Control of Hypertension in Pregnancy Study (CHIPS) trial data. Setting: International multicentre randomised controlled trial (RCT). Population: In all, 987 women with non‐severe non‐proteinuric pregnancy hypertension. Methods: We evaluated the association between pre‐eclampsia definitions and adverse pregnancy outcomes, stratified by hypertension type and blood pressure control. Main outcome measures: Main CHIPS trial outcomes: primary (perinatal loss or high‐level neonatal care for >48 hours), secondary (serious maternal complications), birthweight <10th centile, severe maternal hypertension, delivery at <34 or <37 weeks, and maternal hospitalisation before birth. Results: Of 979/987 women with informative data, 280 (28.6%) progressed to pre‐eclampsia defined restrictively by new proteinuria, and 471 (48.1%) to pre‐eclampsia defined broadly as proteinuria or one/more maternal symptoms, signs or abnormal laboratory tests. The broad (versus restrictive) definition had significantly higher sensitivities (range 62–79% versus 36–50%), lower specificities (range 53–65% versus 72–82%), and similar or higher diagnostic odds ratios and 'true‐positive' to 'false‐positive' ratios. Stratified analyses showed similar results. Addition of available fetoplacental manifestations (stillbirth or birthweight <10th centile) to the broad pre‐eclampsia definition improved sensitivity (74–87%). Conclusions: A broad (versus restrictive) pre‐eclampsia definition better identifies women who develop adverse pregnancy outcomes. These findings should be replicated in a prospective study within routine healthcare to ensure that the anticipated increase in surveillance and intervention in a larger number of women with pre‐eclampsia is associated with improved outcomes, reasonable costs and congruence with women's values. Tweetable abstract: A broad (versus restrictive) pre‐eclampsia definition better identifies the risk of adverse pregnancy outcomes. Tweetable abstract: A broad (versus restrictive) pre‐eclampsia definition better identifies the risk of adverse pregnancy outcomes. This article includes Author Insights, a video abstract available at https://vimeo.com/rcog/authorinsights16602